FORMATION OF LEADERSHIP QUALITIES IN STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS MAJORINGS IN HUMANITIES - Aleksieienko-Lemovska, Liudmyla (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article examines the peculiarities of the formation of leadership qualities in students of humanitarian specialties, the specifics of the organization of the educational process of a higher education institution. Leadership qualities of a modern specialist are described: general professional, creative, socio-psychological, socio-communicative. The components that define a leader are highlighted. The main personality traits of the future specialist are structured by components: communicative, organizational, gnostic, and constructive. It was determined that the leadership is considered to be a internal state of a motivated person, aimed at achieving success, confident in decisions, purposeful in professional activities. Leadership qualities of an individual are defined as a direct condition for the realization of leadership. Development of the methodology for the formation of leadership qualities on the basis of personal responsibility is based on activity, person-oriented, axiological, system, and competence approaches, the principle of development. The types of technologies that are most effectively used for personal development are presented. It was determined that the psychological and pedagogical conditions for the effective development of leadership qualities of students of humanitarian specialties in a higher education institution are: consideration of individual psychological characteristics and development of students' leadership motivation; development of responsibility; creation of a developmental personal-oriented environment; ensuring targeted development of leadership qualities of future specialists. It is necessary to take into account the features of the social environment, the specifics of professional activity and the challenges facing future specialists